The New Turkey: The Spread of Turkish Military Bases Abroad, Role and Indications 2002-2020 - Banisalamah, Mohammad Abdelrahman; Al-Hamadi, Mariam Ibrahim (Dirasat: Human and Social Sciences, 2023)
Objectives: This study aims to answer and investigate the following questions: What is the reason for having Turkish military outside Turkey, including the hosting of Turkish military bases abroad? Do these bases reflect Turkey’s desire to expand its influence and assert its leadership role in the Middle East? Do they reflect a new vision for Turkey as an international actor with a centrally coordinated foreign policy? The researchers pose these questions in light of Turkey’s growing role in the Middle East, as indicated by its trend towards using public diplomacy to enhance its external relations in the regional and international environment, play a more active role, and assume a more effective strategic position. Methods: To answer the research questions, the researchers followed a theoretical approach, conducted an in-depth search using the national interest theory approach and the "strategic depth" theory. Results: Results: According to our investigation, we concluded that Turkey’s location and history make it ready to move positively in all directions, especially within its geographical neighborhood, to preserve its security and achieve its interests. Thus, the decades-long Turkish boycott of the Middle East region and its issues had to end. Consequently, Turkey began to establish military bases in African or Arab countries that are either politically fragile or in need of external protection from their opponents and neighbors. This helped to counter the growing influence of some regional and international powers, enhance Turkish presence, and advance Turkey’s political, economic, and military interests. Conclusion: This study concludes that the construction of Turkish military bases abroad was a response to the increasing influence of certain regional and international powers.